Continuous Renal Replacement Therapy for Two Neonates With Hyperammonemia - Markham, Christopher; Williams, Caroline; Miller, Cory; Grange, Dorothy K.; Davis, T. Keefe; Remy, Kenneth E. (Frontiers in Pediatrics, 2021)
Objectives: This study aims to assess the feasibility of using hemofiltration for ammonia clearance in low body weight infants with an inborn error of metabolism. Design: A study of two cases. Setting: Quaternary pediatric hospital (Saint Louis Children's Hospital) NICU and PICU. Patients: Infants <6 months of age with an ICD-9 diagnosis of 270.6 (hyperammonemia). Interventions: Continuous renal replacement therapy (CRRT). Measurements and Main Results: We measure serum ammonia levels over time and the rate of ammonia clearance over time. Continuous renal replacement therapy was more effective than scavenger therapy alone (Ammonul™) for rapid removal of ammonia in low weight infants (as low as 2.5 kg). Conclusions: Continuous renal replacement therapy is technically feasible in low weight infants with severe hyperammonemia secondary to an inborn error of metabolism.